Village studies in Bangladesh - Hye, Hasnat Abdul (Bangladesh Academy for Rural Development, 1985)
Papers and proceedings of the Workshop on Village Studies in Bangladesh, organized by the Bangladesh Academy for Rural Development, Comilla, 10th-11th April 1985.